Pengembangan Karakter Wirausaha Dalam Pelajaran Ekonomi Bagi Guru Ekonomi Di Kota Padang - Sri Arita; Susi Evanita; Rita Syofyan (Jurnal Ecogen, 2020)
In the industry 4.0 era, it requires individual skills and abilities to continue to exist and be able to keep up with developments in the economy which will be dominated by technology. Humans are no longer required to become workers but are required to create a jobs, therefore it takes the character of entrepreneurship in individuals so as not to position themselves as job seekers who will be defeated by technology, but are expected to become job creators who will be supported by technological developments. The character of the entrepreneur can be instilled through learning or education. The teacher as a facilitator in learning can incorporate elements of entrepreneurial character into economic subjects. The character of the entrepreneur is the locus of control, willing to take risks, creativity and the ability to build good social relationships. To achieve this, learning in high school must be planned in several stages, first, implemented and controlled to achieve the objectives, namely; produce graduates who have an entrepreneurial mind, secondly, habituating the application of entrepreneurship through teaching and learning activities, applying characteristic values and integrating entrepreneurship into learning, third, teaching and learning activities are carried out through planning to open entrepreneurial insights, instill entrepreneurial attitudes, provide practical knowledge and provide knowledge the initial experience of trying, by involving students in learning, is expected to instill concepts, instill attitudes, technical understanding and provide entrepreneurial experience. Keywords : character, entrepreneurial character, education, economy